Unmet supportive care needs of breast, colorectal and testicular cancer survivors in the first 8 months post primary treatment: A prospective longitudinal survey. (22nd August 2021) - Batehup, Lynn; Gage, Heather; Williams, Peter; Richardson, Alison; Porter, Katerina; Simmonds, Peter; Lowson, Elizabeth; Dodson, Lynne; Davies, Nicola; Wagland, Richard; Winter, Jane; Turner, Andrew; et al.
Abstract: Objectives: To explore the supportive care needs of cancer survivors, the characteristics of patients with high levels of unmet need, changes in unmet need after treatment ends and differences in unmet needs of breast, colorectal and testicular survivors. Methods: The method used was a prospective longitudinal mailed survey. Unmet needs, measured by 25‐item modified Cancer Survivors Unmet Needs survey at baseline (immediately post‐treatment) and 8 months later, were analysed descriptively. Results: Of 434 breast, 186 colorectal and 75 testicular patients responding at baseline, 56.2%, 65.6% and 50.7%, respectively, had no unmet needs, the top decile having ≥10 (breast) or seven (colorectal and testicular) different needs and seven different unmet needs. The most frequently reported unmet need (all groups) was fear of cancer recurrence. Unmet needs fell significantly at 8 months for breast patients. Some patients reported new needs. Needs were lowest amongst colorectal survivors and differed between the three groups. Higher levels of unmet needs (breast and colorectal) were associated with having had chemotherapy. Conclusion: Most survivors reported few unmet needs, but a small proportion have persisting or emerging needs. Routine or regular monitoring of unmet needs is required so that healthcare professionals can deliver personalised care based on individual needs, preferences and circumstances.